أسلمة ترجمة المصطلحات الإسلامية إلى الإنجليزية في ضوء الإيبستمولوجيا المعرفية = The Islamization of the translation of Islamic terms into English in the light of cognitive epistomology - Mohammad Idrees, Mohammad Umar Hafiz; Ali, Asem Shehadeh Saleh (University of Jordan, 2025)
Objectives: This study is aimed to understand the emergence of the terminology of Islamization and its development; and to state the role played by the epistemology in the Islamization of knowledge; and to clarify the idea of Islamization of English language in the light of epistemology; and to explain the methodology of Islamization of English language in the light of epistemology; and to discuss the idea of Islamization of English language in the light of epistemology.